Social policy and citizenship. Dialogues between feminist theory and childhood studies - Llobet, Valeria LLOBET (Frontera Norte, 2017)
Este artículo señala algunos desafíos para los estudios de infancia en América Latina y la utilidad de los estudios feministas sobre el Estado. El argumento central propone que relaciones intergeneracionales y categorías etarias constituyen ejes de construcción y legitimación de la desigualdad social. Así, las políticas para la infancia no sólo son escenarios centrales a la construcción de la categoría “infancia”, sino también un espacio donde las dimensiones culturales de las políticas desempeñan un papel en los mentados procesos de legitimación y producción de desigualdad infantil. Por ello, los aportes de las teóricas feministas del bienestar permiten una mejor comprensión de estos procesos. Social policy and citizenship. Dialogues between feminist theory and childhood studies ABSTRACT This article indicates some of the challenges for childhood studies in Latin America and the usefulness of feminist studies on the state. The central argument posits that inter-generational relations and age categories constitute axes for the construction and legitimization of social inequality. Thus, childhood policies are not only central scenarios for the construction of the category of “childhood” but also a sphere where the cultural dimensions of policies play a role in the processes of the legitimization and production of childhood inequality. The contributions of feminist welfare theorists therefore provide a better understanding of these processes